CCAFS approach for climate information services inspired a rural development program in Burkina Faso - CGIAR Research Program on Climate Change, Agriculture and Food Security (2017)
The CCAFS Climate Information Services in West Africa project, in collaboration with meteorological services, radio stations, and mobile phone companies, was instrumental to the development of a component dedicated to the use and dissemination of climate information for VALPAPE program in Burkina Faso. A study tour to was organised to the Climate-Smart Villages of Tibtenga (Burkina) and Cinzana (Mali), made up of a group of 20 people from local communities, agricultural services, farmers' associations, national extension services and agricultural research.